2018
DOI: 10.1051/matecconf/201814505012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of composite coatings of chromium and nanodiamonds on aluminum

Abstract: Abstract. Aluminum offers engineers weight saving advantages in their product design. However, aluminum has poor wear and friction properties. In addition, the surface oxide layer of this chemically active metal, which gives it the corrosion resistance, makes it a very difficult metal to plate [1]. Specific pre-treatment must be applied to remove the oxide layer from the aluminum surface. The nanodiamond particles additionally facilitates the process of chromium deposition. The object of this study is to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The electrochemical chromium coatings, modified with diamond nanoparticles, deposited on wrought steel, sintered steel and other metals and alloys increase several times their hardness, wear and corrosion resistance in comparison to the monochromium coatings. Our studies unambiguously showed the influence of the diamond nanoparticles in improvement of the chemical and mechanical properties of the composite Cr + ND coatings [1][2][3]. The role of the diamond nanoparticles in the built-up of the coatings and their presence in the layer are controversial.…”
Section: Introductionmentioning
confidence: 65%
“…The electrochemical chromium coatings, modified with diamond nanoparticles, deposited on wrought steel, sintered steel and other metals and alloys increase several times their hardness, wear and corrosion resistance in comparison to the monochromium coatings. Our studies unambiguously showed the influence of the diamond nanoparticles in improvement of the chemical and mechanical properties of the composite Cr + ND coatings [1][2][3]. The role of the diamond nanoparticles in the built-up of the coatings and their presence in the layer are controversial.…”
Section: Introductionmentioning
confidence: 65%
“…The deposition of nickel coatings with TiO 2 nanoparticles on aluminum alloys increases their hardness and corrosion resistance [12]. Modified with diamond nanoparticles chromium coating applied on aluminum alloys enhances the mechanical and chemical properties of their surface [13,14].…”
Section: Introductionmentioning
confidence: 99%